2013
DOI: 10.1186/1297-9716-44-16
|View full text |Cite
|
Sign up to set email alerts
|

Equine herpesvirus type 1 infection induces procoagulant activity in equine monocytes

Abstract: The alphaherpesvirus, equine herpesvirus type 1 (EHV-1), is a highly prevalent cause of equine infectious abortion and encephalomyelopathy. These syndromes have been attributed to ischemic necrosis from thrombosis in placental and neural vessels, although the mechanisms underlying thrombosis are unknown. After inhalation, EHV-1 establishes a peripheral blood mononuclear cell-associated viremia, with monocytes being a target of infection. Monocytes are also the main source of tissue factor (TF) in diseased stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 64 publications
3
18
0
Order By: Relevance
“…In addition, Ebola virus infection induces TF expression in lymphoid macrophages and circulating blood cells, which is associated with Ebola haemorrhagic fever [21,24]. In this study, we confirm that in vitro, EHV-1 infection of PBMCs increases TF procoagulant activity, as was shown previously [11]. Our studies are the first to examine this relationship in infected horses, and the results support that PBMCs isolated from EHV-1 infected horses show increased TF procoagulant activity during acute infection (Fig 3).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, Ebola virus infection induces TF expression in lymphoid macrophages and circulating blood cells, which is associated with Ebola haemorrhagic fever [21,24]. In this study, we confirm that in vitro, EHV-1 infection of PBMCs increases TF procoagulant activity, as was shown previously [11]. Our studies are the first to examine this relationship in infected horses, and the results support that PBMCs isolated from EHV-1 infected horses show increased TF procoagulant activity during acute infection (Fig 3).…”
Section: Discussionsupporting
confidence: 90%
“…Stimulation of PBMCs with either EHV-1 at a MOI of 5 for 24 h (Fig 1) or 100 ng/mL of LPS for 6 h (Fig 1) significantly increased FXa activity (P<0.05) indicating that in vitro exposure of PBMCs to either EHV-1 or LPS results in measurable increases in TF procoagulant activity, confirming previous results by Stokol et al and Yeo et al [10,11].…”
Section: Tf Activity Was Significantly Increased In Pbmcs After Ehv-1supporting
confidence: 89%
“…The cause of the documented hypercoagulability and thrombosis in EHV-1-infected horses is unknown, but is likely multifactorial, involving release or upregulation of procoagulants, such as tissue factor, with endothelial injury or vasculitis. We have also previously shown that EHV-1 induces tissue factor expression in equine monocytes (9). Because tissue factor is the main activator of coagulation in vivo (10), upregulated expression of tissue factor on monocytes could be one trigger of the hypercoagulable state.…”
Section: Introductionmentioning
confidence: 72%
“…An alternative possible explanation of DD‐production during EHV‐1 viremia has been recently suggested by Yeo et al. They describe significantly increased release of tissue factor from EHV‐1‐infected equine monocytes in vitro when compared to uninfected monocytes . As the percentage of infected PBMC is very low during EHV‐1 viremia and the monocyte is not the predominant virus carrier during viremia, these interesting findings warrant further investigation …”
Section: Discussionmentioning
confidence: 88%